EXPLORING TEACHERS’ PERSPECTIVE IN USING WHATSAPP APPLICATION IN ENGLISH LANGUAGE TEACHING - Ida Yulianawati; Natalia Anggrarini (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract This research aims to report the teachers’ perspectives in using WhatsApp application in English language Teaching. This qualitative research employed case study by distributing the questionnaire and interview to five participants who used the WhatsApp Application in online English teaching and learning. This study reported that the comfortable, the reasonable cost of internet data, and the ease of communicating with the students were the importance of use of WhatsApp. The strengths of this application covered on the easy and practical application to share the information (schedule and time flexibility), the practical medium to explain the material and set the instruction before, during and post activity of teaching and learning English. The limitation of the WhatsApp covered in term of incomplete features in the WhatsApp application that the students have in their phone, some language skills that are not maximally practiced by the students, the rules that cannot be covered by the teachers and students in learning assessment and incautious checking of the students when the rules is missing. Thus, this study implied the cautious attention from the teachers on the planning, implementing and evaluation for the online teaching and learning of English. Keywords: WhatsApp Application, Online Learning, Teachers’ Perspectives